2021
DOI: 10.3390/biomedicines9111645
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Heart Failure: Insights from Gene Transfer Studies

Abstract: Under physiological circumstances, there is an exquisite balance between reactive oxygen species (ROS) production and ROS degradation, resulting in low steady-state ROS levels. ROS participate in normal cellular function and in cellular homeostasis. Oxidative stress is the state of a transient or a persistent increase of steady-state ROS levels leading to disturbed signaling pathways and oxidative modification of cellular constituents. It is a key pathophysiological player in pathological hypertrophy, patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 124 publications
(177 reference statements)
0
16
0
Order By: Relevance
“…Several studies have reported that DOX tends to induce the generation of ROS during metabolism [ 50 , 51 ]. Compared with other tissues, the myocardium is more vulnerable to oxidative stress, possibly due to low levels of antioxidant enzymes that scavenge ROS [ 52 , 53 ]. Consistent with previous studies, our results confirmed that DOX promoted ROS production in the myocardium of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that DOX tends to induce the generation of ROS during metabolism [ 50 , 51 ]. Compared with other tissues, the myocardium is more vulnerable to oxidative stress, possibly due to low levels of antioxidant enzymes that scavenge ROS [ 52 , 53 ]. Consistent with previous studies, our results confirmed that DOX promoted ROS production in the myocardium of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The top three keywords in frequency in the past decade are apoptosis (216 times), oxidative stress (213 times), and fibrosis (192 times), respectively ( Figure 9 ). Diabetes is characterized by oxidative stress and low-grade inflammation ( 59 ). Under physiological circumstances, a delicate balance between the production and degradation of ROS resulting an average steady-state ROS level.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia also potentiates cardiac hypertrophy and adverse remodeling following myocardial infarction [ 31 , 62 ] and in the setting of diabetic cardiomyopathy [ 63 ]. Oxidative stress and nitro-oxidative stress may play a key role in the effects of hypercholesterolemia on cardiac structure and function [ 64 , 65 , 66 ]. Hypercholesterolemia also induces hyperactive mammalian target of rapamycin (mTOR) signaling in the heart, whereby protein synthesis and cell growth are promoted by the mTOR complex 1 (mTORC1) [ 22 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may clarify why oxidative stress was elevated in apo E deficient mice even in the absence of TAC. Since inflammation [ 72 ] and oxidation [ 66 ] contribute to the development of heart failure, this may explain why apo E deficiency per se may be a potent potentiator of pressure-induced heart failure. Increased oxidative stress may also underlie diastolic dysfunction in C57BL/6N apo E −/− sham mice [ 73 ].…”
Section: Discussionmentioning
confidence: 99%